PEMIKIRAN TEOLOGI ISLAM MODERN PERSPEKTIF SAYYID AHMAD KHAN - Putri, Widdia (JURNAL AL-AQIDAH, 2019)
This paper departs from the assumption that the study of Islamic theology does not touch aspects of reality, so it is still a hot debate among Islamic thinkers. Although theology has progressed from classical to modern– whose discussion has touched on aspects of reality, this assumption never disappears. If classical Islamic theology is incapable of confronting the problem of reality, then modern Islamic theology is able to answer the problem of reality. Sayyid Ahmad Khan is one of the modern Islamic theologians who contributed his thoughts for the betterment of his people. The concept of modern Islamic theology put forward by Sayyid Ahmad Khan became a revival of the spirit of Islam that was lost in India. This is evidence that theological problems can overcome worldly problems. The thought of modern Islamic theology Sayyid Ahmad Khan is first, placing reason in a high position; this is in line with the thought of Muktazilah. But for him, freedom of reason has limits. Second, human actions. Regarding this Sayyid Ahmad Khan is in line with the understanding of Qadariyyah. According to him, human progress depends on the extent to which humans use the resources that God has given him. Third, the law of cause and effect (sunnatullah), according to him Islam is the religion that is most in accordance with natural law because natural law is God's creation and the Qur'an is His word, of course both are in line and there is no contradiction. Keywords: Modern Islamic Theology, Sayyid Ahmad Khan, Islamic Awakening